Negative electrode active material for non-aqueous electrolyte secondary batteries, and non-aqueous electrolyte secondary batteries
Patent Information
- Application Number
- JP2024517308
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-26
- Filing Date
- 2023-04-24
- Publication Date
- 2026-10-22
- Estimated Expiration
- 2043-04-24
Smart Images

Figure 0007940006000002 
Figure 0007940006000003 
Figure 0007940006000001
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a negative electrode active material for a non-aqueous electrolyte secondary battery, and to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, Si-based materials have been used as negative electrode active materials in non-aqueous electrolyte secondary batteries from the perspective of increasing capacity. Patent Document 1 discloses a technique for suppressing short circuits during nail-piercing tests in a negative electrode containing a Si-based material, by forming a framework in the negative electrode mixture layer with a framework-forming agent containing a silicate having siloxane bonds or a phosphate having aluminophosphate bonds. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2018-85276 [Overview of the project]
[0004] However, using the technology described in Patent Document 1, the conductivity of the negative electrode may decrease due to the skeleton formed by the skeleton-forming agent, and the battery capacity may decrease with repeated charging and discharging. Patent Document 1 does not consider the balance between battery safety and charge-discharge cycle characteristics, and there is still room for improvement.
[0005] The purpose of this disclosure is to provide a non-aqueous electrolyte secondary battery with excellent safety and charge / discharge cycle characteristics.
[0006] One aspect of the present disclosure of a negative electrode active material for a non-aqueous electrolyte secondary battery includes a Si-containing composite material, characterized in that the Si-containing composite material includes a matrix in which Si fine particles are dispersed in a matrix phase and GaN coated on the surface of the matrix particles.
[0007] A non-aqueous electrolyte secondary battery according to one aspect of the present disclosure is characterized by comprising a negative electrode containing the above negative electrode active material for non-aqueous electrolyte secondary batteries, a positive electrode, and a non-aqueous electrolyte.
[0008] According to the negative electrode active material for non-aqueous electrolyte secondary batteries of the present disclosure, the safety and charge-discharge cycle characteristics of a non-aqueous electrolyte secondary battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] [Figure 1] It is an axial cross-sectional view of a cylindrical secondary battery that is an example of an embodiment. [Figure 2] It is a cross-sectional view of a Si-containing composite material in an example of the embodiment. DETAILED DESCRIPTION OF EMBODIMENTS
[0010] Hereinafter, an example of an embodiment of a cylindrical secondary battery according to the present disclosure will be described in detail with reference to the drawings. In the following description, specific shapes, materials, numerical values, directions, and the like are examples for facilitating understanding of the present invention, and can be appropriately modified according to the specifications of the secondary battery. In the following, a cylindrical secondary battery in which a wound electrode assembly is housed in a cylindrical exterior body is illustrated, but the electrode assembly is not limited to the wound type, and may be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked one by one with separators interposed therebetween. The exterior body is not limited to a cylindrical shape, and may be, for example, a prismatic shape, a coin shape, or the like. Further, the exterior body may be a pouch type configured from a laminate sheet including a metal layer and a resin layer. In this specification, the description of "numerical value (A) to numerical value (B)" means that the value is equal to or greater than numerical value (A) and equal to or less than numerical value (B).
[0011] FIG. 1 is a cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. As shown in FIG. 1, the secondary battery 10 includes a wound-type electrode assembly 14, a non-aqueous electrolyte, and an outer can 16 that houses the electrode assembly 14 and the non-aqueous electrolyte. The electrode assembly 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The outer can 16 is a bottomed cylindrical metal container that is open on one side in the axial direction, and the opening of the outer can 16 is closed by a sealing assembly 17. Hereinafter, for convenience of description, the side of the sealing assembly 17 of the battery is defined as the upper side, and the bottom side of the outer can 16 is defined as the lower side.
[0012] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode assembly 14 are all strip-shaped long bodies, and are alternately laminated in the radial direction of the electrode assembly 14 by being spirally wound. The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other. The negative electrode 12 is formed to have a size slightly larger than that of the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the longitudinal direction and the width direction (lateral direction). The two separators 13 are formed to have a size at least slightly larger than that of the positive electrode 11, and are arranged, for example, so as to sandwich the positive electrode 11. The electrode assembly 14 includes a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0013] Insulating plates 18 and 19 are respectively arranged above and below the electrode assembly 14. In the example shown in FIG. 1, the positive electrode lead 20 extends to the sealing assembly 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing assembly 17 by welding or the like, and the cap 27, which is the top plate of the sealing assembly 17 electrically connected to the internal terminal plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 serves as a negative electrode terminal.
[0014] A gasket 28 is provided between the outer casing 16 and the sealing body 17 to ensure airtightness inside the battery. The outer casing 16 has a grooved portion 22 formed on its side surface, which protrudes inward to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the outer casing 16, and its upper surface supports the sealing body 17. The sealing body 17 is fixed to the upper part of the outer casing 16 by the grooved portion 22 and the open end of the outer casing 16 which is crimped to the sealing body 17.
[0015] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are stacked in order from the electrode body 14 side. Each component constituting the sealing body 17 has, for example, a disc shape or a ring shape, and each component except the insulating member 25 is electrically connected to one another. The lower valve body 24 and the upper valve body 26 are connected at their respective centers, with the insulating member 25 interposed between their respective peripheries. When the internal pressure of the battery rises due to abnormal heat generation, the lower valve body 24 deforms and breaks, pushing the upper valve body 26 towards the cap 27, thereby interrupting the current path between the lower valve body 24 and the upper valve body 26. If the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0016] The following describes in detail the positive electrode 11, negative electrode 12, separator 13, and non-aqueous electrolyte that constitute the secondary battery 10, with particular attention paid to the negative electrode 12.
[0017] [Negative electrode] The negative electrode 12 includes, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. Preferably, the negative electrode mixture layer is formed on both sides of the negative electrode current collector. The negative electrode current collector can be made of a metal foil that is stable in the negative electrode potential range, such as copper, or a film with the metal arranged on its surface. The negative electrode mixture layer includes, for example, a negative electrode active material and a binder. The negative electrode 12 can be manufactured, for example, by coating a negative electrode mixture slurry containing a negative electrode active material and a binder on both sides of the negative electrode current collector, drying it to form a negative electrode mixture layer, and then rolling this negative electrode mixture layer.
[0018] Examples of the binder contained in the negative electrode mixture layer include fluorine-based resins, polyimide-based resins, acrylic-based resins, polyolefin-based resins, polyacrylonitrile (PAN), styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or a salt thereof, polyacrylic acid (PAA) or a salt thereof (PAA-Na, PAA-K, etc., which may be a partially neutralized salt), polyvinyl alcohol (PVA), and the like. These may be used alone, or two or more types may be used in combination.
[0019] The negative electrode active material contained in the negative electrode mixture layer includes a Si-containing composite material 30. FIG. 2 shows a cross-sectional view of the Si-containing composite material 30 in an example of the embodiment. As shown in FIG. 2, the Si-containing composite material 30 includes mother particles 35 in which Si fine particles 32 are dispersed in a mother phase 34, and GaN 36 coated on the surfaces of the mother particles 35. Thereby, the safety and charge-discharge cycle characteristics of the secondary battery can be improved. It is presumed that the GaN 36 coating the surface improves the thermal conductivity of the Si-containing composite material 30, and enhances the safety of the secondary battery. In general, coating the surfaces of the mother particles 35 with a compound such as a semiconductor degrades the charge-discharge cycle characteristics, but studies by the inventors of the present application have revealed that the charge-discharge cycle characteristics do not specifically degrade when coated with GaN 36.
[0020] The mother particles 35 have, for example, a sea-island structure in which the Si fine particles 32 are substantially uniformly dispersed in the mother phase 34. The mother phase 34 is constituted by, for example, an aggregate of finer particles than the Si fine particles 32. The content of the Si fine particles 32 is, for example, 30 mass% to 70 mass% with respect to the total mass of the mother particles 35.
[0021] The mother phase 34 is, for example, a silicate phase. The mother phase 34 may be a lithium silicate phase. The lithium silicate phase is, for example, represented by the general formula Li 2z SiO (2+z) It is composed of a compound represented by (0<z<2). The mother phase 34 may be a silicon oxide (SiO₂) phase. Further, the mother phase 34 may be an amorphous carbon phase.
[0022] The mother particle 35 may have a carbon film 38 on its surface. This improves the conductivity of the Si-containing composite material 30. As shown in Figure 2, the carbon film 38 may be present in a dotted manner so as to cover at least a portion of the surface of the particle consisting of Si fine particles 32 and the mother phase 34, or it may be present so as to cover the entire surface of the particle consisting of Si fine particles 32 and the mother phase 34. The thickness of the carbon film 38 is preferably 1 nm to 200 nm in order to achieve both conductivity and diffusion of Li ions into the particle interior.
[0023] If the mother particle 35 has a carbon film 38 on its surface, it is preferable that the GaN 36 covers at least a portion of the surface of the carbon film 38. In this case, the GaN 36 may also cover the surface of the mother particle 35 where the carbon film 38 is not present. As shown in Figure 2, the GaN 36 may be present in a dotted manner so as to cover at least a portion of the surface of the mother particle 35, or it may be present so as to cover the entire surface of the mother particle 35.
[0024] In the Si-containing composite material 30, when the mass of the mother particles 35 is 100 parts by mass, the mass of GaN 36 is preferably 10 to 20 parts by mass. When the amount of GaN 36 is within this range, the effects of GaN described above become more pronounced.
[0025] The negative electrode active material contained in the negative electrode composite layer may include, for example, graphite in addition to the Si-containing composite material 30. Examples of graphite include natural graphite such as flaky graphite, lump-shaped artificial graphite, and artificial graphite such as graphitized mesophase carbon microbeads. Furthermore, the negative electrode active material may also include metals that alloy with lithium, such as Si and Sn, or alloys containing these.
[0026] The proportion of Si-containing composite material 30 in the negative electrode active material is preferably 1% to 15% by mass relative to the total mass of the negative electrode active material. When the proportion of Si-containing composite material 30 is within this range, the effects of GaN described above become more pronounced.
[0027] The method for forming the GaN 36 coating on the surface of the base particle 35 is not particularly limited, and for example, vapor deposition, sputtering methods and the like can be used. The GaN 36 is preferably formed by a sputtering method. The GaN 36 is formed, for example, by performing sputter film formation while causing the base particle 35 to flow. Examples of the method for causing the base particle 35 to flow include rotating or vibrating a container accommodating the base particle 35.
[0028] [Positive Electrode] The positive electrode 11 includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer is preferably formed on both surfaces of the positive electrode current collector. For the positive electrode current collector, a foil of a metal that is stable in the potential range of the positive electrode such as aluminum, a film having the metal disposed on its surface layer, and the like can be used. The positive electrode mixture layer contains, for example, a positive electrode active material, a binder, a conductive agent and the like. The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive agent and the like to both surfaces of a positive electrode current collector, drying the applied slurry to form a positive electrode mixture layer, and then rolling the positive electrode mixture layer.
[0029] Examples of the positive electrode active material include lithium transition metal oxides containing transition metal elements such as Co, Mn, and Ni. The lithium transition metal oxide is, for example, Li x CoO2, Li x NiO2, Li x MnO2, Li x Co y Ni 1-y O2, Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4, Li x Mn 2-y M yO4, LiMPO4, Li2MPO4F (M is at least one selected from Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0<x≦1.2, 0<y≦0.9, 2.0≦z≦2.3). These may be used singly or in combination of two or more. In terms of enabling high capacity of the non-aqueous electrolyte secondary battery, the positive electrode active material is Li x NiO2, Li x Co y Ni 1-y O2, Li x Ni 1-y M y O z (M is at least one selected from Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0<x≦1.2, 0<y≦0.9, 2.0≦z≦2.3) and the like, preferably containing a lithium-nickel composite oxide.
[0030] Examples of the conductive agent include carbon-based particles such as carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, and graphite. These may be used alone or in combination of two or more.
[0031] Examples of the binder include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyimide resins, acrylic resins, polyolefin resins, and polyacrylonitrile (PAN). These may be used alone or in combination of two or more.
[0032] [Separator] For the separator 13, for example, a porous sheet having ion permeability and insulating properties can be used. Specific examples of porous sheets include microporous thin films, woven fabrics, and nonwoven fabrics. Suitable materials for the separator include polyethylene, olefin resins such as polypropylene, and cellulose. The separator 13 may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. Alternatively, it may be a multilayer separator containing a polyethylene layer and a polypropylene layer, or a separator 13 with a material such as aramid resin or ceramic coated on its surface may be used.
[0033] [Non-aqueous electrolytes] A non-aqueous electrolyte is a liquid electrolyte (electrolyte solution) containing a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of non-aqueous solvents include esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixtures of two or more of these. The non-aqueous solvent may also contain halogen-substituted solvents in which at least some of the hydrogen atoms in the solvent are replaced with halogen atoms such as fluorine.
[0034] Examples of the above esters include cyclic carbonate esters such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; linear carbonate esters such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylic acid esters such as γ-butyrolactone and γ-valerolactone; and linear carboxylic acid esters such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.
[0035] Examples of the above ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, and crown ethers, as well as chain ethers such as 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0036] As the above halogen-substituted products, it is preferable to use fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylic acid esters such as methyl fluoropropionate (FMP), and the like.
[0037] The electrolyte salt is preferably a lithium salt. Examples of the lithium salt include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10, LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borates such as Li2B4O7, Li(B(C2O4)F2), LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 Examples include imide salts such as SO2){l,m are integers of 1 or more}. Lithium salts may be used individually or in mixtures of multiple types. Of these, LiPF6 is preferred from the viewpoint of ionic conductivity and electrochemical stability. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per liter of solvent. [Examples]
[0038] The present disclosure will be further illustrated by the following examples, but the present disclosure is not limited to these examples.
[0039] <Example 1> [Fabrication of the positive electrode] As the positive electrode active material, powdered LiNi 0.88 Co 0.09 Al 0.03 A lithium transition metal oxide represented by O2 was used. 95 parts by mass of positive electrode active material, 2.5 parts by mass of acetylene black (AB), and 2.5 parts by mass of polyvinylidene fluoride (PVDF) were mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a positive electrode mixture slurry. This positive electrode mixture slurry was applied to both sides of a positive electrode current collector made of aluminum foil, and after the coating film was dried, the coating film was rolled using a rolling roller to produce a positive electrode in which positive electrode mixture layers were formed on both sides of the positive electrode current collector.
[0040] [Fabrication of Si-containing composite materials] SiO2 and Li2CO3 were mixed so that the Si:Li atomic ratio was 1.05:1. This mixture was then calcined at 950°C for 10 hours in an atmospheric environment to obtain lithium silicate represented as Li2O·2.1SiO2. Next, the obtained lithium silicate was pulverized to an average particle size of 10 μm.
[0041] This lithium silicate (Li2O·2.1SiO2) and raw material Si (3N, average particle size 10 μm) were mixed in a 50:50 mass ratio. Next, this mixture was filled into a SUS pot (volume 500 mL) of a planetary ball mill (Frutsch, P-5), and 24 SUS balls with a diameter of 20 mm were placed in the pot. Compounding treatment was carried out at 200 rpm for 50 hours under an inert atmosphere. Furthermore, the compounded mixture was fired at 600°C for 4 hours under an inert atmosphere to obtain a sintered body of particles in which Si fine particles were dispersed in the lithium silicate phase.
[0042] The sintered body was crushed, passed through a 400 μm mesh, coal pitch (JFE Chemical Co., Ltd., MCP250) was added, and then the mixture was fired at 800°C for 5 hours in an inert atmosphere to produce mother particles with a carbon coating on the surface. The amount of carbon coating was 5% by mass relative to the total mass of the mother particles. Subsequently, the mother particles were crushed and classified using an air-flow classifier. The average particle size of the mother particles after classification was 10 μm.
[0043] Next, a Si-containing composite material was fabricated by coating the surface of the mother particles with GaN using the sputtering method. Specifically, 100g of mother particles were placed in the vacuum chamber of a sputtering apparatus, and sputtering was performed using a 5-inch diameter GaN target in the RF method. The amount of GaN deposited was 20% by mass relative to the mass of the mother particles. Sputtering was performed under an Ar gas flow environment after evacuating the vacuum chamber until the pressure was 1.8 Pa, and then reducing the pressure to approximately 1 Pa. The deposition temperature was 1000°C. Furthermore, sputtering was performed while the mother particles were flowed by rotating the container containing them. After sputtering, the mother particles were crushed and classified using an airflow classifier to produce a Si-containing composite material with an average particle size of 10 μm.
[0044] [Fabrication of the negative electrode] The above Si-containing composite material and graphite with an average particle size of 22 μm were mixed in a mass ratio of 4.8:95.2 to prepare the negative electrode active material. 100 parts by mass of the negative electrode active material, 1 part by mass of carboxymethylcellulose (CMC), and 1 part by mass of styrene-butadiene copolymer rubber (SBR) were mixed, and the mixture was kneaded in water to prepare a negative electrode mixture slurry. The negative electrode mixture slurry was applied to both sides of a negative electrode current collector made of copper foil, and after the coating film was dried, the coating film was rolled with a rolling roller to produce a negative electrode in which a negative electrode mixture layer was formed on both sides of the negative electrode current collector.
[0045] [Preparation of non-aqueous electrolytes] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a non-aqueous solvent prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7.
[0046] [Manufacturing of secondary batteries] An electrode body was fabricated by attaching an aluminum positive electrode lead to a positive electrode current collector and a nickel negative electrode lead to a negative electrode current collector, and then spirally winding the positive and negative electrodes together via a polyolefin separator. This electrode body was housed in a bottomed cylindrical battery case body with an outer diameter of 18.2 mm and a height of 65 mm, and after injecting the non-aqueous electrolyte, the opening of the battery case body was sealed with a gasket and a sealing body to produce an 18650 type cylindrical secondary battery.
[0047] <Example 2> In the preparation of the Si-containing composite material, a secondary battery was fabricated in the same manner as in Example 1, except that the amount of GaN film deposited was changed to 10% by mass relative to the mass of the parent particles.
[0048] <Example 3> A secondary battery was fabricated in the same manner as in Example 1, except that the mass ratio of the Si-containing composite material and graphite constituting the negative electrode active material was changed to 15:85.
[0049] <Example 4> A secondary battery was fabricated in the same manner as in Example 1, except that the amount of GaN film deposited in the Si-containing composite material was changed to 10% by mass relative to the mass of the parent particles, and the mixing ratio of the Si-containing composite material and graphite constituting the negative electrode active material was changed to a mass ratio of 15:85 in the fabrication of the negative electrode.
[0050] <Example 5> A secondary battery was fabricated in the same manner as in Example 1, except that the mixing ratio of the Si-containing composite material and graphite constituting the negative electrode active material was changed to a mass ratio of 2.8:97.2.
[0051] <Comparative Example 1> A secondary battery was fabricated in the same manner as in Example 1, except that a GaN film was not deposited in the Si-containing composite material.
[0052] <Comparative Example 2> A secondary battery was fabricated in the same manner as in Example 1, except that GaN was not deposited in the Si-containing composite material, and in the fabrication of the negative electrode, the mixing ratio of the Si-containing composite material and graphite constituting the negative electrode active material was changed to a mass ratio of 4.0:95.2, and GaN powder was added to the negative electrode active material so that the mass ratio of the negative electrode active material to GaN powder was 99.2:0.8.
[0053] <Comparative Example 3> In the preparation of the Si-containing composite material, a secondary battery was fabricated in the same manner as in Example 1, except that the target for sputter deposition was changed and Ga2O3 was deposited instead of GaN.
[0054] <Comparative Example 4> In the preparation of the Si-containing composite material, a secondary battery was fabricated in the same manner as in Example 1, except that the target for sputter deposition was changed to deposit AlN instead of GaN.
[0055] <Comparative Example 5> In the fabrication of the Si-containing composite material, a secondary battery was manufactured in the same manner as in Example 1, except that the target for sputter deposition was changed and SiC was deposited instead of GaN.
[0056] <Comparative Example 6> In the fabrication of the Si-containing composite material, a secondary battery was prepared in the same manner as in Example 1, except that the target for sputter deposition was changed and Si3N4 was deposited instead of GaN.
[0057] [Nail-piercing test] The following procedure was used to perform a nail-piercing test on each battery in the examples and comparative examples. (1) Under conditions of 25°C, constant current charging was performed at 0.5C until the battery voltage reached 4.2V, and then constant voltage charging was performed at 4.2V until the current value was reduced to 1 / 50C. (2) Under conditions of 25°C, the side temperature of the rechargeable battery charged in (1) was measured while inserting a 2mm diameter iron nail into the center of its side at a speed of 5mm / second, and the highest temperature at that time was determined. (3) If the secondary battery did not rupture or catch fire and the maximum temperature was 100°C or lower, it was evaluated as "○". If the secondary battery did not rupture or catch fire but the maximum temperature exceeded 100°C, it was evaluated as "△". If the secondary battery ruptured or caught fire, it was evaluated as "×".
[0058] [Cycle Test] Under an ambient temperature of 25°C, the secondary batteries of each example and comparative example were charged with a constant current of 0.5C until the battery voltage reached 4.2V, and then charged with a constant voltage of 4.2V until the current value was reduced to 1 / 50C. Afterward, they were discharged with a constant current of 0.5C until the voltage reached 2.85V. This charge-discharge cycle was considered one cycle, and a cycle test was performed for 200 cycles. The capacity retention rate of the secondary batteries of each example and comparative example during the charge-discharge cycle was determined using the following formula. Capacity retention rate = (Discharge capacity at 200 cycles / Discharge capacity at 1 cycle) × 100
[0059] Table 1 summarizes the evaluation results of the nail penetration test and cycle test for each secondary battery in the examples and comparative examples. Table 1 also shows the type and amount of coating material used in the Si-containing composite material, as well as the proportion of Si-containing composite material in the negative electrode active material.
[0060] [Table 1]
[0061] The secondary battery in the example showed better results in the nail-piercing test and equivalent or better capacity retention compared to the secondary battery in Comparative Example 1. On the other hand, Comparative Example 2, in which GaN was incorporated into the negative electrode mixture layer without coating the Si-containing composite material, showed a lower capacity retention than the secondary battery in Comparative Example 1. Furthermore, the secondary batteries in Comparative Examples 3 to 6, which used Si-containing composite materials coated with materials other than GaN, did not yield results that satisfied both the nail-piercing test and capacity retention. These results indicate that coating the surface of the mother particles with GaN can improve safety in secondary batteries without degrading the charge-discharge cycle characteristics.
[0062] This disclosure is further illustrated by the following embodiments. Configuration 1: A negative electrode active material for a non-aqueous electrolyte secondary battery, comprising a Si-containing composite material, The Si-containing composite material comprises a matrix in which Si fine particles are dispersed in a matrix phase, and GaN coated on the surface of the matrix particles, and is a negative electrode active material for a non-aqueous electrolyte secondary battery. Configuration 2: The aforementioned mother particles are negative electrode active materials for a non-aqueous electrolyte secondary battery according to configuration 1, wherein the mother particles have a carbon coating on their surface. Configuration 3: The negative electrode active material for a non-aqueous electrolyte secondary battery according to configuration 2, wherein the GaN covers at least a portion of the surface of the carbon film. Configuration 4: The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of configurations 1 to 3, wherein the matrix phase is a silicate phase. Configuration 5: The aforementioned matrix phase is lithium A silicate phase, a negative electrode active material for a non-aqueous electrolyte secondary battery as described in any one of configurations 1 to 3. Configuration 6: The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of configurations 1 to 3, wherein the matrix phase is an amorphous carbon phase. Composition 7: The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of configurations 1 to 6, wherein, in the Si-containing composite material, when the mass of the mother particles is 100 parts by mass, the mass of the GaN is 10 to 20 parts by mass. Composition 8: The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of the configurations 1 to 7, wherein the proportion of the Si-containing composite material in the negative electrode active material for a non-aqueous electrolyte secondary battery is 1% by mass to 15% by mass with respect to the total mass of the negative electrode active material for a non-aqueous electrolyte secondary battery. Composition 9: A non-aqueous electrolyte secondary battery comprising a negative electrode containing a negative electrode active material for non-aqueous electrolyte secondary batteries as described in any one of configurations 1 to 8, a positive electrode, and a non-aqueous electrolyte. [Explanation of Symbols]
[0063] 10 Non-aqueous electrolyte secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 16 Outer casing, 17 Sealing body, 18,19 Insulating plate, 20 Positive electrode lead, 21 Negative electrode lead, 22 Grooved section, 23 Internal terminal plate, 24 Lower valve body, 25 Insulating material, 26 Upper valve body, 27 Cap, 28 Gasket, 30 Si-containing composite material, 32 Si fine particles, 34 Matrix phase, 35 Mother particles, 36 GaN, 38 Carbon coating
Claims
1. A negative electrode active material for a non-aqueous electrolyte secondary battery containing a Si-containing composite material, The Si-containing composite material comprises a matrix in which Si fine particles are dispersed in a matrix phase, and GaN coated on the surface of the matrix particles, and is a negative electrode active material for a non-aqueous electrolyte secondary battery.
2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the mother particles have a carbon coating on their surface.
3. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 2, wherein the GaN covers at least a portion of the surface of the carbon film.
4. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the matrix phase is a silicate phase.
5. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the matrix phase is a lithium silicate phase.
6. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the matrix phase is an amorphous carbon phase.
7. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein, in the Si-containing composite material, when the mass of the mother particles is 100 parts by mass, the mass of GaN is 10 to 20 parts by mass.
8. The anode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the proportion of the Si-containing composite material in the anode active material for a non-aqueous electrolyte secondary battery is 1% by mass to 15% by mass with respect to the total mass of the anode active material for a non-aqueous electrolyte secondary battery.
9. A non-aqueous electrolyte secondary battery comprising a negative electrode containing the negative electrode active material for a non-aqueous electrolyte secondary battery described in any one of claims 1 to 8, a positive electrode, and a non-aqueous electrolyte.
Citation Information
Patent Citations
High-safety dendrite-free lithium metal battery as well as preparation method and application thereof
CN112768695A
Skeleton forming agent and negative electrode using the same
JP2018085276A
Negative electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery
WO2016035290A1
Nonaqueous electrolyte secondary battery negative electrode and nonaqueous electrolyte secondary battery
WO2020066576A1